Canibalismo en la Cueva de Malamuerzo : identificación de huellas de manipulación intencional en restos óseos humanos de origen arqueológico (Granada, España) - Solari Giachino, Ana (BAR international series, 2012)
"This volume focuses on: the identification of indelible traces recorded on bones; on human actions associated with these marks; and finally on human behaviours that led to actions performed on bodies around the time of death. The research joins a long line of studies focused on cannibalism recognition, as one of the behaviours associated with death carried out by different social groups at all times and places. The methodology is based on the observation of a series of intentional manipulation traces left in bone's surfaces, and the examination of modifications caused by taphonomic agents or non-human factors that may interfere with right interpretation of the agent responsible for this behaviour. Complex funerary practices, violent deceases, human sacrifices, offerings of human remains or cannibalism are behaviours associated with death that leave a series of recognizable marks on bones. These marks are a result of the treatment to which human bodies were subjected around the time of death. This diversity of behaviour leads to a variety of body treatments, such as skinning, disarticulation, defleshing, cooking, etc, which, in turn, causes a multiplicity of visible bone changes allowing observation, recording, and systematization to researchers. This study entailed the re-examination of the human bones recovered at Malalmuerzo cave where traces of cannibalism were noticed on Neolithic samples."--Publisher's web site.